Government of India Bill - India Government (New Delhi : Manager of Publications, 1935)
It is proposed in this Bill to make provision for the transfer to Votes of Parliament of the expenses of the Establishment of the Secretary of State (Clauses 264 (5), 266 (1), 267 (2), (3), (5) and (6), 431 (5) and 432 (3)). Pro vision is made for the payment of contributions from the revenues of India and Burma in respect of so much of the expenses of the India Office as is attributable to the per formance on behalf of India and of Burma of such agency functions as it may be agreed between the Secretary of State and the Governor-General of India and the Governor of Burma that the India Office should perform. The amount of the contribution payable in this regard will be agreed between the Governor-General and the Trea sury (Clause 266 (3)) and the Governor of Burma and the Treasury (Clause 432 (1)). A contribution will also be made from the revenues of India in respect of the superannua tion allowances, etc., of the India Office staff transferred (Clause 268 (1)).
Keywords: Constitutional law